'I've got my eyes open and I can't be crooked': Race, female virtue and national identity in Terry and the Pirates. (1st April 2018) - Martin, Catherine
The Second World War-era US network radio programmes augmented nationalist propaganda by connecting American national identity to white patriarchal gender norms. Juvenile adventure radio serials like Terry and the Pirates (TATP) joined this effort and countered criticism of their negative influence on children by promoting their ability to teach young audiences socially sanctioned values like respect for established authority and cultural norms. Within this cultural and industrial context, characters like April Kane became 'discursive "relay station[s]"' through which wartime debates over women's changing cultural and economic status were circulated, contested and produced. TATP tested April's dedication to an idealized American way of life by pairing and contrasting her with queered and exoticized racial others, including sexually deviant female criminals and subservient foreign men. April passed this inquisition by identifying with Burma, the series' other white heroine, and adhering to traditional feminine values like honesty, passivity and deference to white patriarchal authority. These comparisons reaffirmed a gendered hierarchy that prioritized white men and simultaneously diminished and divided white women and foreign men.